Spatiotemporal Variations of Summertime Compound Hot and Dry Events in China and the Associated Atmospheric Circulations Using Daily Threshold Indices - Huixin Li; Anqin Tan; Jiani Zeng; Botao Zhou; Qiuxiao Zhu; Yi Fan; Yuan Yuan (International Journal of Climatology, 2026)
Under global warming, compound hot‐dry events (CHDEs) pose increasing threats across China. This study investigates the spatiotemporal characteristics of summer CHDEs and their monthly atmospheric drivers using two independent datasets (CN05.1 and satellite‐based) during 1979–2022. A daily‐scale Compound Hot‐Dry Index (CHDI) is developed to identify co‐occurring high‐temperature and low‐precipitation extremes. Results show that the climatological frequency of CHDEs is highest in Northwest China, while the most pronounced increasing trends are found in Southwest China. Rotated empirical orthogonal function analysis of monthly CHDI fields reveals a coherent monthly shift in the dominant mode of variability: the primary centre of action migrates from Northwest China in June to Northern China in July, and finally to the Yangtze River Valley in August. Dynamical diagnosis indicates this progression is governed by distinct teleconnection patterns. The June pattern is driven by a Rossby wave train associated with the silk road pattern (SRP), which establishes an equivalent‐barotropic Central Asian ridge, inducing subsidence and blocking moisture to favour CHDEs in the northwest. In July, the dominant mode is linked to the Polar‐Eurasian (POL) pattern, sustaining a Baikal High that promotes heating over Northern China while anomalous easterlies impede Pacific moisture transport. By August, an intensified and westward‐extended western Pacific subtropical high becomes the key driver, causing subsidence and disrupting the monsoon flow to trigger CHDEs in the Yangtze River Valley. These findings highlight a robust monthly progression in CHDE dynamics, offering a process‐based framework for understanding compound extremes in a warming climate.